2013
DOI: 10.4161/rna.23590
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of small RNAs inYersinia pestis

Abstract: Yersinia pestis, the etiologic agent of plague, is closely related to Yersinia pseudotuberculosis evolutionarily but has a very different mode of infection. The RNA-binding regulatory protein, Hfq, mediates regulation by small RNAs (sRNAs) and is required for virulence of both Y. pestis and Y. pseudotuberculosis. Moreover, Hfq is required for growth of Y. pestis, but not Y. pseudotuberculosis, at 37°C. Together, these observations suggest that sRNAs play important roles in the virulence and survival of Y. pest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 38 publications
4
52
1
Order By: Relevance
“…While there exists some overlap in the sRNA sets discovered in each of these studies, there are a large number of potential sRNAs that are unique to each study. Recently, Beauregard et al identified 15 previously unannotated sRNAs in the KIM6ϩ strain of Y. pestis (33). This group also identified several previously annotated sRNAs and multiple Ysrs described in our previous study; we subsequently detected in Y. pestis CO92 the expression of 2 Ysrs found in the KIM6ϩ strain (Ysr164 and Ysr172).…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…While there exists some overlap in the sRNA sets discovered in each of these studies, there are a large number of potential sRNAs that are unique to each study. Recently, Beauregard et al identified 15 previously unannotated sRNAs in the KIM6ϩ strain of Y. pestis (33). This group also identified several previously annotated sRNAs and multiple Ysrs described in our previous study; we subsequently detected in Y. pestis CO92 the expression of 2 Ysrs found in the KIM6ϩ strain (Ysr164 and Ysr172).…”
Section: Discussionsupporting
confidence: 52%
“…This group also identified several previously annotated sRNAs and multiple Ysrs described in our previous study; we subsequently detected in Y. pestis CO92 the expression of 2 Ysrs found in the KIM6ϩ strain (Ysr164 and Ysr172). A second report identified 104 sRNAs in Y. pestis strain 201 from both in vitro-and in vivo-derived samples, and 56 of these were not identified by our previous study or by the study of Beauregard et al (33). In the current study, only one of the sRNAs identified (Ysr222 or sR049) was also detected by Yan et al (35).…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…The expression profile data were obtained from microarray hybridization experiments, 32 and the sRNA data were obtained from RNA-seq results. 18 In addition, data from related literatures, including MS data from the KIM, CO92, and PestoidesF strains, and sRNA data from the 91001 and KIM strains, 33,34 were collected manually.…”
Section: Methodsmentioning
confidence: 99%